Treatment With Intravenous Alteplase for Acute Ischemic Stroke After Reversal of Dabigatran With Idarucizumab: A Case Study. Issue 1 (February 2019) - Jala, Sheila; O'Brien, Elizabeth
Abstract : ABSTRACT: Treatment options for anticoagulated patients presenting with ischemic stroke are limited. Off-label use of idarucizumab to rapidly reverse the anticoagulant effect of dabigatran may ensure eligibility for thrombolytic therapy with alteplase. This case describes a 77-year-old white male who presented to the hospital 89 minutes after sudden onset of right-sided hemiparesis, dysarthria, and facial palsy. Significant history included atrial fibrillation and previous right-sided cortical stroke. Medication reconciliation revealed he was taking dabigatran 150 mg twice a day, with the last dose being 179 minutes before presentation. Neuroimaging revealed no new infarct or hemorrhage, and 60 minutes after arrival, a decision was made to give idarucizumab to reverse the anticoagulant effect of dabigatran. In the absence of any contraindication, he was then treated with intravenous alteplase and idarucizumab. No adverse outcomes were noted, and at discharge, his new stroke symptoms were completely resolved.